APPLIED HR ENGINEERING TOOLS IN THE AUTOMATED SYSTEM FOR STRATEGIC MANAGEMENT OF ENTERPRISE HUMAN RESOURCES POTENTIAL - Novalska , N. I.; Dokiienko , L. M.; Klymenko , V. V. (Systems and Technologies, 2026)
The article is devoted to the study of the practical application of HR engineering tools for systemic and strategic management of the enterprise’s human resources. An analysis of HR engineering as a holistic tool for strategic design of the architecture of personnel processes in an organization, which integrates business strategy directly into the structure of HR processes, is carried out. The theoretical basis of HR engineering is considered, in particular the role of HR engineering in the digital architecture of the enterprise and the principles of its implementation. An analysis of key segments and tools of the digital HR ecosystem is carried out. The importance of taking into account differences in the legislation of Ukraine and other countries when making a decision on the use of foreign tools of the digital HR ecosystem in the practical activities of domestic enterprises is substantiated. An example of the interdependence of the functioning of digital tools of the socio-technical system based on an automated employee development cycle using the “Performance Management” module is shown. A comparative characteristic of HRM systems that are actively used on the Ukrainian market as platforms for engineering management processes is provided. An algorithm for the practical implementation of HR engineering has been developed, in particular the stages of HR process redesign from the “as is” audit to the “to be” design. The qualitative transformation of HR processes before and after the redesign has been visualized. A comparative characteristic of HR processes in the “as is” and “to be” models has been presented. The issue of the economic efficiency of implementing automated HR processes based on HR engineering has been considered, in particular, the performance indicators of using modern digital technologies in the process of personnel management. Examples of the use of HRM systems in the practice of foreign and domestic enterprises in various fields of business activity have been studied